A review on Advances in Biomarker-Based Detection Strategies for Ovarian Cancer - Doppalapudi Prasanthi; Yeramanchi Sarah Sujitha; Adepu Geetha Susmita; G Naveena; Seelam veenasri; Ayyavaripalli Sandhya Rani; Dr. S. Prabagar (The Bioscan, 2025)
Globally, ovarian cancer ranks as the eighth leading cause of cancer-related mortality among women. As a result of inadequate symptoms in its early stages, most cases are diagnosed at advanced stages, where treatment becomes more challenging. Standard therapeutic approaches primarily surgical tumor reduction followed by systemic chemotherapy is often hindered by the emergence of chemoresistance, affecting nearly three-quarters of patients and resulting in poor clinical outcomes. This underscores the urgent need to re-evaluate existing biomarkers and discover new ones that can enhance diagnostic accuracy and prognostic assessment. Biomarkers capable of identifying disease presence, progression, and treatment responsiveness could significantly improve early detection and patient survival rates. This review explores currently validated ovarian cancer-specific biomarkers and highlights innovative technologies and methodologies being employed to uncover novel diagnostic and prognostic indicators. Although symptoms such as abdominal discomfort, bloating, and urinary or bowel changes may suggest disease onset, they are frequently vague and nonspecific. Age, inherited genetic mutations, and a family history of cancer are recognized as key contributors to ovarian cancer risk. Promising biomarkers like CA-125, HE4, osteopontin, and genetic profiling are being investigated for early detection. Diagnosis typically involves imaging techniques and histopathological confirmation via biopsy. Treatment strategies vary based on cancer stage and type, encompassing surgery, chemotherapy, and targeted therapies. Timely diagnosis and effective intervention rely heavily on routine screenings and heightened awareness of potential warning signs. KEYWORDS ovarian cancer, biomarkers, risk factors, DNA-repair pathways, cell signaling mechanisms, cell-cycle related genes.